Control de malezas en caña de azúcar. - Gómez Peña, J.F.; Sánchez Emers, O.; Buenaventura Osorio, C. E.; Ranjel Jiménez, H.; Ayalde Varón, G. (Instituto Colombiano Agropecuario, 2018)
Caña de azúcar-Saccharum officinarum